Enhanced Store-Operated Calcium Entry in Platelets is Associated with Peripheral Artery Disease in Type 2 Diabetes - Weijie Xia; Yingsha Li; Bin Wang; Jing Chen; Xiaojing Wang; Qianqian Sun; Fang Sun; Zhiyong Li; Zhigang Zhao (Cellular Physiology and Biochemistry, 2015)
Background/Aims: Platelet dysfunction plays an important role in thrombosis in diabetes with peripheral artery disease (PAD). Store-operated calcium entry (SOCE) and stromal interaction molecule 1 (STIM1) regulate platelet activity by modulating calcium influx. We hypothesized that enhanced SOCE in platelets is associated with diabetes with PAD. Methods: We studied the activity of platelets from healthy participants and from type 2 diabetic patients. Platelet calcium influx and protein expression of STIM1 and sarcoendoplasmic reticulum Ca2+-ATPase 3 (SERCA3) were investigated. Results: Compared with platelets from diabetic patients without PAD, platelets from diabetic patients with PAD exhibited significantly increased SOCE . Menthol administration completely inhibited calcium influx in platelets from diabetic patients without PAD, but this effect was blunted in those from diabetic patients with PAD. Furthermore, the increase in SOCE was correlated with the ankle brachial index (ABI) in diabetic patients. High glucose significantly up-regulated STIM1 and SERCA3 protein expression and induced the phosphorylation of phospholipase C (PLC) in platelets from healthy participants. This effect was attenuated in the presence of menthol or U73122, an inhibitor of PLC. Similarly, significant increases in STIM1 and SERCA3 protein expression were found in platelets from diabetic patients compared to those from healthy participants. Conclusion: Platelets from diabetic patients with PAD exhibited enhanced Store-operated calcium influx, which was associated with elevated STIM1/SERCA3 expression via a PLC-dependent pathway and was inhibited by menthol.